Babo's Strategy in the Development of Islamic Education in Madrasah Tarbiah Diniyah Thailand - Srinio, Fuad; Sebgag, Saliha; Hali, Ali Usman; Usman, Muhammad Umair Khan (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This article aims to describe the role and strategy of Babo (Kyai) in developing Islamic education in Madrasah Tarbiah Diniyah Thailand. This article uses qualitative research methods with a case study approach. The data obtained was done by observation, interview, and documentation in Madrasah Tarbiah Diniyah Thailand. The important findings of this article are to show that (1) Babo's role in developing education when becoming an educator Babo is not only a teacher and educator but also a leader and manager of the boarding school to survive in the face of modernization and Babo must be able to adjust his education in the boarding school so that his students have character or character under the mission carried out in Islam (2) Strategies in developing education Babo always applies an integration process between methods, techniques, tactics in determining learning strategies. Babo combines various strategies such as Uswah Hasanan, exemplary, and habituation.